Enhanced Four‐Wave Mixing in Silicon Nitride Waveguides Integrated with 2D Layered Graphene Oxide Films. Issue 23 (19th October 2020) - Qu, Yang; Wu, Jiayang; Yang, Yunyi; Zhang, Yuning; Liang, Yao; El Dirani, Houssein; Crochemore, Romain; Demongodin, Pierre; Sciancalepore, Corrado; Grillet, Christian; Monat, Christelle; Jia, Baohua; et al.
Abstract: Layered 2D graphene oxide (GO) films are integrated with silicon nitride (SiN) waveguides to experimentally demonstrate an enhanced Kerr nonlinearity via four‐wave mixing (FWM). SiN waveguides with both uniformly coated and patterned GO films are fabricated based on a transfer‐free, layer‐by‐layer GO coating method along with standard photolithography and lift‐off processes, yielding precise control of the film thickness, placement, and coating length. Detailed FWM measurements are carried out for the fabricated devices with different numbers of GO layers and at different pump powers, achieving up to ≈7.3 dB improvement in the FWM conversion efficiency for an uniformly coated device with one layer of GO and ≈9.1 dB for a patterned device with five layers of GO. A detailed analysis of the influence of pattern length and position on the FWM performance is performed. The dependence of GO's third‐order nonlinearity on layer number and pump power is also extracted, revealing interesting physical insights about the layered 2D GO films. Finally, an enhancement is obtained in the effective nonlinear parameter of the hybrid waveguides by over a factor of 100 relative to bare SiN waveguide. These results demonstrate the high nonlinear optical performance of SiN waveguides integrated with layered 2D GO films. Abstract : Layered 2D graphene oxide films are integrated with silicon nitride waveguides to experimentally demonstrate enhanced Kerr nonlinearity via four‐wave mixing (FWM). Up to 7.3 and 9.1 dB improvements of FWM conversion efficiency are achieved for the uniformly coated device and patterned device, respectively. The influence of pattern length and position on the FWM performance is also analyzed.